Detection, molecular typing and phylogenetic analysis of Leishmania isolated from cases of leishmaniasis among Syrian refugees in Lebanon. (c2015) - Salloum, Tamara (2015)
Leishmania is a parasitic protozoan with more than two-dozen species causing the disease leishmaniasis. It is transmitted to humans through the bite of an infected female phlebotomine sand-fly. In the past two years the incidence of leishmaniasis has been drastically increasing in Lebanon. This was in parallel with the deterioration of the security in Syria forcing thousands to flee seeking shelter at refugee camps in Lebanon. Water, sanitation and hygiene facilities in those collective shelters are far from adequate, increasing the risk and turning those camps into fertile grounds for the spread of diseases. Cutaneous leishmaniasis (CL) is now considered a public health problem, but its epidemiology has not been fully elucidated. A crucial point in containing the disease is first Leishmania species identification and then correlation with clinical parameters. In this study, two molecular typing methods for Leishmania speciation were used along with sequencing and phylogenetic analysis. The parasites identified were all Leishmania tropica as determined by both the ITS1-PCR RFLP and the nested ITS1-5.8S rDNA gene amplification. ITS1-5.8S rDNA gene based typing proved to be more sensitive in the detection of parasites (positive in 70% of the isolates) as opposed to the ITS1-PCR RFLP method that was successful in identifying Leishmania in only 47.4% of the isolates. Sequencing and phylogenetic analysis revealed high levels of heterogeneity among the sequenced isolates. To our knowledge, this is the first study using two different molecular methods for the detection and identification of L. tropica in Lebanon. The obtained results could be used for accurate detection and diagnosis of Leishmania in CL and for tracing possible changes in the population structure of L. tropica.